The refurbishment of gasometers as a relevant witness of industrial archaeology. (1st February 2015) - Fiorino, Luigi; Landolfo, Raffaele; Mazzolani, Federico Massimo
Highlights: Gasometers are, in some cases, constructions of significant historical and cultural interest. The attention is focused on relevant European examples of gasometers recovering. The structural restoration design of the 80, 000 m 3 of Naples is illustrated. Abstract: The term gasometer, coined by the inventor of gas lighting William Murdoch in the late 18th century, is commonly used to indicate a structure for storing gas. Nowadays, the gasometers have a significant historical and cultural interest, belonging to the so-called "industrial archaeology". The most important gasometer typologies are illustrated in this paper, by focusing on relevant European examples of structural recovering and functional conversion evidences, such as the gasometers of Vienna, Oberhausen (Germany), Dresden, Leipzig, Copenhagen, Dublin and Athens. Finally, the main aspects concerning the restoration design of the 80, 000 m 3 column-guided telescoping gasometer of Naples are illustrated.